COMPOSITION AND SOURCES OF MAGMAS IN MEDVEZH'YA CALDERA (ITURUP ISLAND, SOUTHERN KURILES) FROM A STUDY OF MELT INCLUSIONS - Kovalenko V.I.; Tsareva G.M.; Naumov V.B.; Tolstykh M.L.; Kononkova N.N. (My University, 2004)
Melt and fluid inclusions are studied in phenocrysts of olivine, pyroxene, plagioclase, and quartz from 14 samples of lavas from the Men'shoǐ Brat and Kudryavyǐ volcanoes (Medvezh'ya caldera, Iturup Island, Southern Kuriles). Homogenization temperatures of melt inclusions are determined for phenocrysts of basalts, basaltic andesites, and andesites (1280-1330°C for olivine, 1070-1265°C for plagioclase, and 1110-1215°C for orthopyroxene) and dacites (900-950°C for plagioclase, clinopyroxene, and quartz). The melt inclusions in olivine (Fo 88-90, close to the mantle olivine) have a picrobasaltic composition (43 wt % SiO 2, 14% MgO, 0.35% K 2O), those in pyroxenes and plagioclases vary from basaltic (49 wt % SiO 2, 7.1% MgO, 0.3% K 2O) through andesitic (61 wt % SiO 2, 3.2% MgO, 1.3% K 2O) to rhyolitic (73 wt % SiO 2, 0.28% MgO, 1.8% K 2O). The inclusions in phenocrysts from dacites have rhyodacitic to rhyolitic compositions. High-K basaltic (52 wt % SiO 2, 4.4% K 2O) and dacitic (65 Wt % SiO 2, 5.3% K 2O) melts are recognized. Volatile concentrations in the melt inclusions vary significantly with the melt composition. The picrobasaltic melts contain 0.07 wt % H 2O, 0.18% S, 0.13% Cl, and 0.08% F. In silicic melts, the S content decreases (0.04 wt %) and the Cl and H 2O contents increase (up to 0.29 and 2.5%, respectively). The melts have trace-element features of island-arc magmas and show high Li/Y, K/La, B/La, La/Nb, and Ba/Nb, which indicate the addition of a subduction-related fluid component to the mantle magma source. The variation of melt compositions and temperatures was controlled by processes of magma generation in different sources variable in K, Ti, P, and Mg contents. The magmas were generated in (a) the mantle wedge that has not been affected by fluids derived from a subducting plate by dehydration (for picrobasaltic melts), (b) the mantle wedge metasomatically altered by such fluids (for andesitic, dacitic, and rhyolitic melts), (c) the mantle wedge containing high-K minerals (amphibole or mica) (for high-K basaltic, andesitic, and rhyodacitic melts), and (d) island-arc crust (probably with sediments) melted under the effect of high-temperature basaltic magmas. The magmas from the specified sources were modified by mixing and crystal fractionation.